Global trends in low back pain and neck pain in the working population: implications for occupational health - Zhao, Yonghui; Wang, Jiqing; Zhao, Boya; Zhang, Yingang (Frontiers in Public Health, 2025)
This study systematically evaluated the global burden of low back pain (LBP) and neck pain (NP) among individuals aged 20–65 from 1990 to 2021, utilizing data from the Global Burden of Disease (GBD) database. We analyzed incidence, prevalence, years lived with disability (YLDs), and age-standardized rates across 204 countries and regions, stratified by socio-demographic index (SDI). Key findings indicate a slight decline in LBP metrics but a mild increase in NP trends, with higher growth rates observed in females. Socioeconomic status significantly influenced these patterns, with developed countries showing lower YLDs increasing rate. The study highlights the need for gender-specific and region-tailored public health strategies, particularly focusing on women in lower SDI countries. These findings underscore the importance of targeted interventions to mitigate the growing burden of LBP and NP in an aging workforce increasingly engaged in office work.